Autochthonous dissolved organic matter potentially fuels methane ebullition from experimental lakes. (1st December 2019) - Zhou, Yongqiang; Zhou, Lei; Zhang, Yunlin; Garcia de Souza, Javier; Podgorski, David C.; Spencer, Robert G.M.; Jeppesen, Erik; Davidson, Thomas A.
Abstract: Shallow lakes are hotspots for carbon processing and important natural sources of methane (CH4 ) emission. Ebullitive CH4 flux may constitute the overwhelming majority of total CH4 flux, but the episodic nature of ebullition events makes determining both quantity and the controlling factors challenging. Here we used the world's longest running shallow-lake mesocosm facility, where the experimental treatments are low and high nutrients crossed with three temperatures, to investigate the quantity and drivers of CH4 ebullition. The mean CH4 ebullition flux in the high nutrient treatment (41.5 ± 52.3 mg CH4 –C m −2 d −1 ) mesocosms was significantly larger than in the low nutrient treatment (3.6 ± 5.4 mg CH4 –C m −2 d −1 ) mesocosms, varying with temperature scenarios. Over eight weeks from June to August covered here warming resulted in a weak, but insignificant enhancement of CH4 ebullition. We found significant positive relationships between ebullition and chlorophyll- a, dissolved organic carbon (DOC), biodegradable DOC, δ 2 H, δ 18 O and δ 13 C-DOC, autochthonous dissolved organic matter (DOM) fluorescent components, and a fraction of lipids, proteins, and lignins revealed using ultrahigh-resolution mass spectrometry, and a negative relationship between ebullitive CH4 flux and the percentage volume inhabited of macrophytes. A 24 h laboratory bio-incubation experiment performed at room temperature (20 ± 2 °C) in the dark further revealed a rapid depletion of algal-DOM concurrent with a massive increased CH4 production, whereas soil-derived DOM had a limited effect on CH4 production. We conclude that eutrophication likely induced the loss of macrophytes and increase in algal biomass, and the resultant accumulation algal derived bio-labile DOM potentially drives enhanced outgassing of ebullitive CH4 from the shallow-lake mesocosms. Graphical abstract: Image 1 Highlights: CH4 ebullition enhanced with increasing Chl- a, DOC, BDOC and autochthonous DOM. Highly biolabile protein-rich components are likely biodegraded from algal scums. Autochthonous algal-derived DOC share enriched δ 2 H, δ 18 O and δ 13 C-DOC. Markedly increased CH4 concurrent with rapid depletion of highly biolabile algal-DOM.